Karakteristik Fisikokimia, Mikrobiologi, dan Uji Pasar Yogurt Smoothies Rosela Stroberi pada Usia Remaja dan Dewasa di Bogor - Putra Jahtra Berutu; Irma Isnafia Arief; Mochammad Sriduresta Soenarno; Lucya Cyrilla Eko Nugrohowati Supriyadi Dekriyatna (Institut Pertanian Bogor, 2023)
Yogurt is a dairy product that is processed into a fermented drink using lactic acid bacteria. Smoothies are drinks made from fruit or vegetables containing milk, yogurt, or honey. Strawberry Rosella Yogurt Smoothie is yogurt that has been processed by reducing the water content and adding rosella flower extract and strawberry jam. Before being marketed, these products need to be tested for safety and market opportunities. This study aims to analyze the physicochemical characteristics, microbiology, and market tests of strawberry rosella yogurt smoothies in adolescents and adults in Bogor. The physicochemical characteristics tested included pH, water activity (aw), viscosity, and total titrated acid. The microbiological parameters tested were total lactic acid bacteria and Salmonella sp. The market parameters tested include analysis of consumer perceptions and preferences and their correlation with yogurt consumption patterns. The market test was carried out using 100 respondents consisting of 50 students from SMAN 1 Bogor and 50 students from IPB University. The results showed that the physical properties (pH, water activity, viscosity, and total lactic acid) fulfilled the SNI yogurt quality requirements. The chemical properties or nutritional content and microbiological properties of yoghurt smoothies have met the requirements for yoghurt quality standards based on SNI. The results showed that respondents had good perceptions and preferences on the attributes of smoothie yogurt. Consumer preferences regarding the appearance of the packaging in general, color, ingredient content, packaging information, and appearance of the contents of the yogurt are generally positively correlated with the price range of yogurt that consumers buy. Strawberry Rosella Yoghurt Smoothie is safe for consumption and can be marketed. Keywords: consumer perception, consumer preferences, microbiology, physicochemistry, yogurt smoothies